Influence Of The Gripping Fixture On The Modified Compact Tension Test Results: Evaluation Of The Experiments On Cylindrical Concrete Specimens - Holušová Táňa; Lozano Miguel; Fernández-Canteli Alfonso; Komárková Tereza; Kocáb Dalibor; Seitl Stanislav (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2015)
The modified compact tension test (MCT) might become in the future a stable test configuration for the evaluation of fracture-mechanics parameters or also for description of fatigue behavior of composites materials such as concrete. Core drilling is used for sampling of existing structures. These samples have cylindrical shape with the selected thickness to avoid the stress concentration. This contribution focuses on the evaluation of the fracture behavior during static and quasi static tests. Static tests are performed on standard specimen with diameter 150 mm and length 300 mm. The quasi-static tests are performed using two different gripping fixtures. The results for quasi-static tests are represented as L-COD diagrams (i.e. load vs. crack opening displacement) measured on the loading axis. The comparison of results and discussion of advantages and disadvantages are introduced.